The Tax Policy from an Economic Growth Perspective - Dorel NOROC (ACROSS)
This article summarizes the evidence on the relationship between tax policy and economic growth, referring to several case studies providing more substance and detail. Potential negative effects of tax policy on economic growth have been addressed in the debates on whether to increase taxes to reduce the deficit and reform taxes by broadening the base to lower tax rates.